ANALISIS PENGARUH INVESTASI LUAR NEGERI DAN INVESTASI DALAM NEGERI TERHADAP PRODUK DOMESTIK BRUTO DI INDONESIA 2017-2021 - Putri Aulia Rizky; Adisti Amelia Tasya; Yunita Rahmadani Harahap; Deris Desmawan (FEB Universitas Maritim Semarang, 2022)
Foreign Investment (PMA) and Domestic Investment (PMDN) are indicators that clearly have influence over the state of the economy in a certain country. The goal of this study is to understand and analyze the impact of asing and local government investments on gross domestic product (PDB). The methodology used is a quantitative method that makes use of second-level data from the Badan Pusat Statistics (BPS). The information used is a time series that spans the years 2017 to 2021. . This study was analyzed using the Classical Assumption test and Multiple Regression With PMA and PMDN serving as variables X or independent variables and PDB serving as variables Y or dependent variables, The results of studies found that foreign investment or (PMA) have no significant impact on GDP, whereas domestic investment or (PMDN) has significant impact on GDP.